(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2021)
This research aimed at determining the reality of the partnership between Russia and the European Union during the period 2000-2019, the extent of the relationship of GDP to foreign trade and the degree of economic openness. The descriptive and analytical approach has been relied on in the analysis of Russia’s tools and policy towards trade exchange and partnership with the European Union. Where the data of GDP, exports and imports, and the trade balance was relied upon to calculate the average annual increase, the average growth rate and the degree of economic exposure. The most important conclusions were Russia’s endeavor to build a partnership with the European Union based on joint cooperation and dealing with issues of security and common neighborhood, promoting and diversifying trade exchanges, and that the Russian economy is not exposed to the European economy. The most important recommendations were represented in the necessity of Russia diversifying its exports to European markets and not relying solely on the export of oil and natural gas.